Solid solution strengthening type maraging stainless steel for low-temperature environment and preparation method of solid solution strengthening type maraging stainless steel

By adding elements such as Co, Mo to martensite aging stainless steel, Ti is removed, Si is increased, and a specific heat treatment process is carried out to form nano-scale reverse transform austenite, which solves the problem of insufficient toughness and fatigue performance in low-temperature environments in the prior art, and achieves high strength and excellent low-temperature performance of the material.

CN119800226APending Publication Date: 2025-04-11NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510074871.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing martensite aging stainless steel fails to meet the performance requirements of large low-temperature high-Reynolds number wind tunnels in low temperature environments, especially in terms of yield strength, impact toughness and fatigue performance.

Method used

By optimizing chemical composition, adding alloying elements such as Co and Mo, removing Ti elements, increasing Si elements, and combining with appropriate heat treatment processes, nano-scale reverse transform austenite is formed, thereby improving the strength and low-temperature performance of solid solution-strengthening martensite aging stainless steel.

Benefits of technology

It significantly improves the impact toughness and fatigue performance of the material at 77K, improves the comprehensive performance of martensite aging stainless steel, and meets the material performance requirements of large low-temperature high-Reynolds number wind tunnels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800226A_ABST
    Figure CN119800226A_ABST
Patent Text Reader

Abstract

The invention provides solid solution strengthening type maraging stainless steel for a low-temperature environment and a preparation method, the stainless steel comprises the following component elements in percentage by weight: 10-12% of Cr, 8-10% of Ni, 6-7% of Co, 3-4% of Mo, 0.2-0.3% of Si, 0.15-0.3% of Mn, and a harmful element Clt; 0.023%, Slt; 0.0029%, Plt; 0.0021%, and the balance being Fe and inevitable impurities. According to the design concept of the solid solution strengthening maraging stainless steel alloy used in the low-temperature environment, solid solution strengthening is mainly used for replacing precipitation strengthening, high strength is guaranteed, and meanwhile the situation that a precipitated phase serves as a crack source to damage the low-temperature toughness and low-temperature fatigue performance of a material is avoided. The method mainly comprises the following steps: removing Ti to avoid the generation of a high-density Ni3Ti intermetallic compound precipitated phase, adding Si, Mo and other elements to reduce the precipitation rate of the Laves precipitated phase, and meanwhile, synergistically adding Co and Mo elements to improve the solid solution strengthening amount of the material and ensure the high strength of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of maraging stainless steel, and in particular to a solid solution strengthened maraging stainless steel for low temperature environment and a preparation method thereof. Background Art

[0002] Maraging stainless steel was born in the middle of the last century. As a typical representative of ultra-high-strength steel, it shines in key pillar fields such as aerospace and clean energy with its excellent comprehensive performance. The construction of large-scale low-temperature and high-Reynolds number wind tunnels is the key to breaking through the "Reynolds gap" between the actual transonic demand and wind tunnel test capabilities in the testing of my country's new generation of aircraft. In the construction of low-temperature wind tunnels, the integrated system composed of supporting structures and test models serving in liquid nitrogen environments is the main body and core. It needs to serve safely for a long time under complex and harsh working conditions such as high aerodynamic loads, wide temperature range (-196℃~25℃), and strong transient impacts, which puts higher requirements on the service performance of maraging stainless steel.

[0003] At present, the test models of conventional wind tunnels are mainly made of 30CrMnSiA, 17-4PH, etc. The large-scale low-temperature and high-Reynolds number wind tunnel jointly built by the Shanghai Institute of Mechanical and Electrical Engineering and the China Aerodynamics Research and Development Center has put forward more stringent requirements on the performance of the test model materials: yield strength ≥1250 MPa at −196°C, V-notch impact energy ≥70J, and fatigue strength ≥700MPa. The main material of the existing wind tunnel support structure is S03 martensitic aging stainless steel (022Cr12Ni10MoTi) developed by the Soviet Union for aircraft engines. At present, the yield strength of S03 steel at room temperature and −196°C can reach 950MPa and 1250MPa respectively, and the V-notch impact energy and fatigue strength do not meet the index requirements.

[0004] It can be seen that how to improve the low-temperature performance of materials to meet the actual needs of large-scale advanced cryogenic projects while ensuring the corrosion resistance of materials is a hot topic in maraging stainless steel research. Therefore, it is urgent to develop new maraging stainless steels that match high and low temperature strength and toughness, especially those with excellent low-temperature fatigue performance. Summary of the invention

[0005] In view of the problems existing in the above-mentioned background technology, the present invention provides a solid solution strengthened maraging stainless steel for low temperature environment and a preparation method thereof. By optimizing the chemical composition of maraging stainless steel, alloying elements such as Co and Mo are added on the basis of Cr and Ni stainless steel to improve the solid solution strengthening effect. At the same time, by removing Ti and adding Si element, the formation rate of precipitated phase Ni3Ti, Laves phase, etc. is reduced. With the appropriate heat treatment process, nano-scale reverse transformation austenite is formed in the material, so that the strength and toughness of the solid solution strengthened maraging stainless steel, especially the impact toughness and fatigue performance at 77K, are significantly improved, and the comprehensive performance of maraging stainless steel is improved.

[0006] Specifically, the first aspect of the present invention provides a solid solution strengthened maraging stainless steel for low temperature environment, wherein the stainless steel is composed of the following component elements by weight percentage: Cr=10~12%, Ni=8~10%, Co=6~7%, Mo=3~4%, Si=0.2~0.3%, Mn=0.15~0.3%, and the balance is Fe and unavoidable impurities.

[0007] As a further illustration of the present invention, in the stainless steel, by weight percentage, C<0.023%, S<0.0029%, and P<0.0021%.

[0008] As a further illustration of the present invention, the stainless steel is composed of the following component elements by weight percentage: Cr=10.75%, Ni=8.09%, Co=6.64%, Mo=2.99%, Si=0.26%, Mn=0.21%, and the balance is Fe and unavoidable impurities.

[0009] The second aspect of the present invention provides a method for preparing the solid solution strengthened maraging stainless steel for low temperature environment described in any one of the above, comprising the following steps: Step 1: Select metals Cr, Co, Mo, Ni, Mn, and Si according to the weight percentage of each element described in any one of the above, and the rest is pure iron and inevitable impurities; Step 2: performing vacuum induction melting on the metal elements obtained in step 1, and then performing vacuum consumable remelting to obtain a casting; Step 3: subjecting the ingot obtained in step 2 to high temperature homogenization treatment to obtain a homogenized ingot; Step 4: rolling the homogenized ingot obtained in step 3 to obtain a slab; Step 5: The slab obtained in step 4 is subjected to solution treatment and aging treatment to obtain martensitic aging stainless steel.

[0010] As a further illustration of the present invention, in step 2, the smelting is carried out in a vacuum induction melting furnace, the vacuum degree throughout the process is ≤0.1 Pa, the refining temperature is 1660~1700MPa, the refining time is ≥1h, and the stirring time is ≥20min.

[0011] As a further illustration of the present invention, during the vacuum consumable remelting process in step 2, the vacuum in the furnace is ≤0.01 Pa throughout the entire process, and the remelting rate is maintained at 150-300 kg / h.

[0012] As a further explanation of the present invention, the high temperature homogenization process is specifically as follows: Heat in air, the heating method is furnace heating, the heating rate is 100~150℃ / h, keep warm at 1200~1300℃ for 2~4h, then cool to room temperature with water.

[0013] As a further explanation of the present invention, the rolling process is specifically as follows: The homogenized ingot is heated to 1200° C., the initial rolling temperature T=1100-1150° C., the final rolling temperature T≥1050° C., and the rolling reduction is ≥80%.

[0014] As a further explanation of the present invention, the solution treatment adopts cyclic solution treatment, specifically: The slab is heated to 750-800°C at a heating rate of 5-10°C / min, kept at this temperature for 0.5h, then cooled to room temperature, and the above solution treatment process is repeated 4 times.

[0015] As a further illustration of the present invention, the aging treatment adopts a two-step treatment, specifically: The first aging treatment temperature is 540~580℃, the aging time is 20~30min, and it is air-cooled to room temperature. The second aging treatment temperature is 480~520℃, the aging time is 40~50min, and it is air-cooled to room temperature.

[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The design concept of the solid solution strengthened martensitic aged stainless steel alloy for low temperature environment provided by the present invention is mainly to replace precipitation strengthening with solid solution strengthening, and to avoid the precipitation phase as a crack source to damage the low temperature toughness and low temperature fatigue performance of the material while ensuring high strength. It mainly includes the removal of Ti to avoid the formation of high-density Ni3Ti intermetallic compound precipitation phase, the addition of elements such as Si and Mo to reduce the precipitation rate of Laves precipitation phase, and the addition of Co and Mo elements to increase the solid solution strengthening amount of the material to ensure the high strength of the material.

[0017] The present invention is more suitable for the industrialized production of large castings and forgings. The addition of elements such as Co and Mo can ensure the hardenability and stability of large castings and forgings. The removal of Ti avoids the generation of large inclusions such as TiN and TiC, which causes instability in low-temperature mechanical properties.

[0018] The maraging stainless steel of the present invention has simple preparation process, wide heat treatment process window, strong process controllability, and excellent low-temperature impact performance and fatigue performance.

[0019] The maraging stainless steel of the present invention has broad application prospects in the fields of low-temperature wind tunnels, oceans, energy, etc.

[0020] Other features and advantages of the technical solution will be described in the subsequent description, and partly become apparent from the description, or understood by implementing the technical solution. The purpose and other advantages of the technical solution can be achieved and obtained through the structures specifically pointed out in the written description and the drawings.

[0021] The technical solution of the present technical solution is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings are used to provide a further understanding of the technical solution and constitute a part of the specification. Together with the embodiments of the technical solution, they are used to explain the technical solution and do not constitute a limitation of the technical solution. In the accompanying drawings: Figure 1 TEM and EDS images of the precipitated phase of the AG560-500 sample after aging for 1 hour in Example 1 of the present invention, wherein (a) is a TEM image and (b) is an EDS image.

[0023] Figure 2 This is a TEM image of the precipitated phase of the AG500-1 sample in Comparative Example 1 of the present invention after aging for 1 hour.

[0024] Figure 3 This is the stress-strain curve of Example 1 of the present invention after aging.

[0025] Figure 4 1 is the impact absorption energy curve of the AG560-500 sample after aging in Example 1 of the present invention, wherein (a) is the impact absorption energy curve at room temperature, and (b) is the impact absorption energy curve at 77K. DETAILED DESCRIPTION

[0026] The preferred embodiments of the present technical solution are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present technical solution, and are not used to limit the present technical solution.

[0027] The invention provides a solid solution strengthened martensitic aging stainless steel for low temperature environment. The stainless steel consists of the following component elements by weight percentage: Cr=10-12%, Ni=8-10%, Co=6-7%, Mo=3-4%, Si=0.2-0.3%, Mn=0.15-0.3%, and the balance is Fe and inevitable impurities.

[0028] Furthermore, in the stainless steel, by weight percentage, C<0.023%, S<0.0029%, and P<0.0021%.

[0029] The alloy composition design reasons of the maraging stainless steel of the present invention are as follows: The Ni element in the present invention, as a forming element of reverse transformation austenite, has a significant effect on improving the hardenability of martensitic aging stainless steel, expanding the austenite phase region, and reducing the Ms point. Since the Ti element is removed in the present invention, the Ni3Ti precipitation phase will not be formed during the aging process, and the Ni element only exerts a solid solution strengthening effect. In addition, the Ni element can increase the transgranular cleavage fracture resistance of the martensitic lath, reduce the intrinsic DBTT value, and improve the low-temperature toughness of the material. However, too high a Ni element content will cause the formation of residual austenite and reduce the strength of the material. Considering comprehensively, the weight percentage of the Ni element is set to 8~10%, for example, it can be set to 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, etc.

[0030] The Cr element in the present invention is an important element to ensure the corrosion resistance of martensitic aging stainless steel. In addition, the Cr element is the main element for the formation of ferrite, and too high a Cr element will cause a decrease in the strength of the material. The setting of the Cr element content should take into account the corrosion resistance and ensure that the Ni equivalent and the Cr equivalent are within the martensite + austenite dual phase region of the Schaeffler phase diagram. The weight percentage of the Cr element is set to 10-12% by comprehensive consideration, for example, it can be set to: 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, etc.

[0031] The Mo element in the present invention is an important strengthening element. On the one hand, the Mo element can play a role in solid solution strengthening, and on the other hand, it can form Laves precipitation phase strengthening during the aging process. In addition, the addition of the Mo element can cooperate with the Cr element to improve the corrosion resistance of the material. Mo can be incorporated into the Cr2O3 passivation film to form a composite passivation film containing Mo, thereby improving the stability and self-repairing ability of the passivation film. The Cr element mainly limits the dissolution of the anode metal by forming a stable oxidation state, while the Mo element can reduce the cathode reaction rate and reduce harmful reactions such as hydrogen precipitation. The two interact with each other to improve the overall corrosion resistance of the material. Considering comprehensively, the weight percentage of the Mo element is set to 3~4%, for example, it can be set to 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, etc.

[0032] The Co element in the present invention can improve the comprehensive properties of the material. The Co element interacts with the Mo element, reduces the nucleation energy of Mo2C precipitation, makes the precipitation phases such as Mo2C finer and evenly distributed in the martensitic matrix, and effectively improves the strength of the material. The Co element is the only element that reduces ferrite and increases the Ms point at the same time, which can promote the complete martensitic phase transformation of the matrix to obtain a low-carbon martensitic lath structure. In addition, the Ni element can reduce the martensitic transformation temperature of the steel, making the martensitic structure finer and more uniform, while the Co element improves the strength by strengthening the matrix and promoting the formation of precipitation phases. The combination of the two enables the material to have good toughness and impact resistance while maintaining a high strength. However, excessive Co content will promote the formation of twins and the generation of Cr-poor areas, reducing the plastic toughness and corrosion resistance of the material. Considering comprehensively, the weight percentage of the Co element is set to 6~7%, for example, it can be set to 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, etc.

[0033] The Si element in the present invention is a beneficial element in martensitic aged stainless steel. The Si element can react with the O element in the molten steel to generate oxide inclusions such as SiO2, reduce the oxygen content in the molten steel, and improve the purity of the material. The synergistic addition of low-diffusion elements such as Si and Mo elements can reduce the precipitation kinetics of the precipitated phase and avoid the coarsening of the precipitated phase. Excessive Si elements can cause brittle phases or grain boundary bonding forces to reduce the toughness of the damaged material. Considering comprehensively, the weight percentage of the Si element is set to 0.2~0.3%, for example, it can be set to 0.20%, 0.22%, 0.24%, 0.26%, 0.28%, 0.30%, etc.

[0034] The Mn element in the present invention is a beneficial element in martensitic aged stainless steel. The Mn element has a strong affinity with the S element, and can preferentially combine to form MnS inclusions, avoiding S and Fe from forming a FeS eutectic phase and causing hot brittleness. At the same time, the Mn element is also an important element that affects the formation of reverse transformed austenite. Too high a content of the Mn element leads to severe segregation of the material, reduced weldability, increased internal stress, and other reductions in material properties. Considering comprehensively, the weight percentage of the Mn element is set to 0.15-0.3%, for example, it can be set to 0.15%, 0.18%, 0.21%, 0.24%, 0.27%, 0.30%, etc.

[0035] The C element in the present invention is a harmful element in martensitic aging stainless steel. On the one hand, it can form an intergranular precipitation phase with the Cr element, promote the depletion of Cr, and reduce the corrosion resistance of the material. On the other hand, during the aging process, MX or M 23 The formation of C6 phase will delay the formation of reverse transformation austenite and reduce the toughness of the material. Therefore, the C content of the maraging stainless steel in the present invention should be as low as possible, and the C content is required to be controlled to C<0.023%.

[0036] The S, P and other elements in the present invention are harmful impurity elements in maraging stainless steel. In order to ensure the toughness of the material at 77K, the content of S and P elements should be as low as possible under the premise of considering the production cost, and the content of S and P elements is required to be controlled to S<0.0029%, P<0.0021%.

[0037] The method for preparing the solid solution strengthened maraging stainless steel for low temperature environment comprises the following steps: Step 1: According to the weight percentage of the above elements, metals Cr, Co, Mo, Ni, Mn, Si are selected, and the rest are pure iron and inevitable impurities; the above metals are all high-purity metals.

[0038] Step 2: The metal elements obtained in step 1 are subjected to vacuum induction melting, and then vacuum consumable remelting to obtain a casting.

[0039] In the above step 2, a vacuum induction melting furnace is used for melting, the vacuum degree is ≤0.1Pa throughout the process, the current frequency and power are accurately controlled, the refining temperature is 1660~1700MPa, the refining time is ≥1h, and the stirring time is ≥20min to ensure that the principle is fully melted and the composition is uniform. After the above composition adjustment, casting is carried out, and the molten metal is smoothly injected into the water-cooled copper mold through the bottom gate or transfer bag.

[0040] In the above step 3, when vacuum consumable remelting is performed, the vacuum in the furnace is ≤0.01Pa throughout the whole process to ensure that the melting is carried out in a low-oxygen and low-impurity atmosphere. The remelting rate is maintained at 150~300kg / h.

[0041] Step 3: subjecting the ingot obtained in step 2 to high temperature homogenization treatment to obtain a homogenized ingot.

[0042] The high temperature homogenization process is specifically as follows: heating in air, the heating method is furnace heating, the heating rate is 100-150°C / h, keeping at 1200-1300°C for 2-4h and then cooling to room temperature with water.

[0043] Step 4: Roll the homogenized ingot obtained in step 3 to obtain a slab.

[0044] The above-mentioned rolling process is specifically as follows: the homogenized ingot is heated to 1200°C, the initial rolling temperature T=1100~1150°C, the final rolling temperature T≥1050°C, the temperature is measured using an infrared thermometer, the rolling reduction is ≥80%, and the width of the slab after rolling is about 120mm.

[0045] Step 5: The slab obtained in step 4 is subjected to solution treatment and aging treatment to obtain martensitic aging stainless steel.

[0046] The above-mentioned solution treatment adopts cyclic solution treatment, specifically: the slab is heated to 750-800°C at a heating rate of 5-10°C / min, kept warm for 0.5h and then cooled to room temperature, and then the above-mentioned solution treatment process is repeated 4 times.

[0047] The above aging treatment adopts a double-step treatment, specifically: the first aging treatment temperature is 540~580℃, the aging time is 20~30min, and air cooling to room temperature; the second aging treatment temperature is 480~520℃, the aging time is 40~50min, and air cooling to room temperature.

[0048] The room temperature mechanical properties of the maraging stainless steel obtained by the above preparation method are: yield strength Rm ≥ 1100MPa, tensile strength ≥ 1200MPa, elongation A ≥ 20%, impact energy ≥ 150J, and low temperature impact energy ≥ 65J.

[0049] The present invention will be further described below in conjunction with specific embodiments: Example 1

[0050] Calculated by weight percentage, the solid solution strengthened maraging steel is a plate containing the following components: Cr=10.75%, Ni=8.09%, Co=6.64%, Mo=2.99%, Si=0.26%, Mn=0.21%, C<0.023%, S<0.0029%, P<0.0021%, and the balance is Fe and unavoidable impurities.

[0051] The preparation method of the above-mentioned solid solution strengthened maraging steel comprises the following steps: The steel ingot is obtained by vacuum induction melting + vacuum consumable melting.

[0052] High temperature homogenization treatment, heating in air, heating method is furnace heating, heating rate is 130℃ / h, keep warm at 1200℃ for 2h and then cool to room temperature with water.

[0053] Rolling treatment, the ingot is heated to 1200℃, the initial rolling temperature T=1150℃, the final rolling temperature T=1050℃, the temperature is measured by infrared thermometer, the rolling reduction is 88%, and the specific rolling procedures are as follows: 100mm→85mm→65mm→45mm→35mm→25mm→17mm→12mm. After seven rolling passes, the width of the slab is about 120mm.

[0054] Cyclic solution treatment was performed, with the plate heated to 750°C at a heating rate of 8°C / min, kept at this temperature for 0.5h, and then cooled to room temperature in water, which was repeated four times.

[0055] Double-step aging treatment, the plate obtained by cyclic solution treatment is subjected to aging treatment under two conditions. In order to facilitate distinction, the plates are divided into sample AG560-500 and sample AG500-500. Specifically: Sample AG560-500 was aged in the following manner: the first aging treatment temperature was 560°C, the aging time was 20 min, and the sample was air-cooled to room temperature. The second aging treatment temperature was 500°C, the aging time was 40 min, and the sample was air-cooled to room temperature. Sample AG500-500 was aged in the following manner: the first aging treatment temperature was 500°C, the aging time was 20 min, and the sample was air-cooled to room temperature. The second aging treatment temperature was 500°C, the aging time was 40 min, and the sample was air-cooled to room temperature. Figure 1 TEM and EDS images of the precipitated phase of sample AG560-500 after aging in Example 1. Only a small amount of Mo-rich precipitated phase can be observed from the image.

[0056] The mechanical properties of Example 1 are shown in Table 2. Figure 3 and Figure 4 They are respectively the stress-strain curve and the room temperature and low temperature impact energy change curves of Example 1. The room temperature yield strength and tensile strength of the AG560-500 sample are 1125MPa and 1230MPa, respectively, the elongation is 28%, the room temperature impact energy is 190J, and the low temperature impact energy is 90J. The room temperature yield strength and tensile strength of the AG500-500 sample are 1140MPa and 1258MPa, respectively, the elongation is 22%, the room temperature impact energy is 158J, and the low temperature impact energy is 68J.

[0057] The fatigue properties of Example 1 at 77K are shown in Table 1.

[0058] Table 1 Cycle times of samples under different heat treatment conditions in Example 1

[0059] The Basquin fatigue life prediction model was used to fit the fatigue strength of Example 1 at 77K. When the stress ratio was 0.1, the fatigue life was greater than 10 7 The fatigue strength of the AG560-500 specimen is 850MPa, which meets the design requirements of the new generation of large-scale high-Reynolds number low-temperature wind tunnels.

[0060] Comparative Example 1 In this comparative example, a vacuum induction furnace is used to smelt precipitation-strengthened maraging stainless steel. Calculated by weight percentage, the precipitation-strengthened maraging steel is a bar containing the following components: Cr=11.73%, Ni=9.70%, Mo=0.78%, Ti=0.23%, Si=0.067%, Mn=0.016%, C=0.0047%, S=0.0042%, P=0.0029%, and the balance is Fe.

[0061] Compared with Example 1, the contents of Si and Mo low diffusion coefficient elements are reduced to 0.067% and 0.78% respectively, and the Ti content is increased to 0.23%. As the main precipitation strengthening element, other harmful elements such as C, S, and P are controlled at a relatively low level.

[0062] The steel ingot was subjected to high temperature homogenization and annealing treatment at 1200°C for 2h and then rolled to obtain stainless steel samples.

[0063] The cyclic solution treatment was carried out by heating the stainless steel sample to 750℃ at a heating rate of 8℃ / min, keeping it at that temperature for 0.5h, then cooling it to room temperature in water, and the cycle was repeated 4 times. The aging treatment was carried out by heating the bar to 500℃ at a heating rate of 4℃ / min, keeping it at that temperature for 1h, 8h, and 64h, and they were named AG500-1, AG500-8, and AG500-64, respectively. Figure 2 This is the TEM image of the precipitate phase of sample AG500-1 after aging. A large number of rod-shaped Ni3Ti precipitates can be observed in the figure.

[0064] The mechanical properties of Comparative Example 1 are shown in Table 2.

[0065] In Comparative Example 1, as the aging time increases, the material strength decreases and the plasticity increases slightly. This is because for the precipitation-strengthened martensitic aging stainless steel, the peak aging window of the precipitation phase is <1h. In the over-aged state, the reverse transformation austenite is accelerated, resulting in a decrease in strength and an increase in plasticity.

[0066] In Comparative Example 1, the tensile strength of the three heat-treated samples is lower than 1200MPa, and the plasticity is poor <10%. The maximum impact energy at room temperature and low temperature is only 137J and 44J. It is also difficult to improve the strength and toughness of the material by using other heat treatments.

[0067] Table 2 Mechanical properties of maraging stainless steel of Example 1 and Comparative Example 1

[0068] Example 1 and Comparative Example 1 show that, compared with conventional precipitation-strengthened maraging stainless steel, the solid solution-strengthened maraging stainless steel for low-temperature environments provided by the present invention has good strength-toughness matching and excellent low-temperature fatigue performance at room temperature and low temperature, and improves the hardenability and stability of the material by element optimization, reduces the damage to the low-temperature performance of the material caused by large-sized inclusions, and greatly shortens the heat treatment process time by optimizing the heat treatment process, so that the present invention is suitable for the industrial production of large castings and forgings.

[0069] In addition, the solid solution strengthened martensitic aging stainless steel for low temperature environment provided by the present invention can meet the performance requirements of large low temperature and high Reynolds number wind tunnel test model materials: yield strength ≥1250 MPa at −196°C, V-notch impact energy ≥70J, fatigue strength ≥700MPa, and therefore has broad application prospects in low temperature wind tunnels, oceans, energy and other fields.

[0070] Obviously, those skilled in the art can make various changes and modifications to the technical solution without departing from the spirit and scope of the technical solution. Thus, if these modifications and variations of the technical solution fall within the scope of the claims of the technical solution and their equivalents, the technical solution is also intended to include these modifications and variations.

Claims

1. A solid solution strengthened maraging stainless steel for low temperature environment, characterized in that: The stainless steel is composed of the following elements by weight: Cr=10~12%, Ni=8~10%, Co=6~7%, Mo=3~4%, Si=0.2~0.3%, Mn=0.15~0.3%, and the balance is Fe and inevitable impurities.

2. The solid solution strengthened maraging stainless steel for low temperature environment according to claim 1, characterized in that: In the stainless steel, by weight percentage, C<0.023%, S<0.0029%, and P<0.0021%.

3. The solid solution strengthened maraging stainless steel for low temperature environment according to claim 1, characterized in that: The stainless steel is composed of the following component elements by weight percentage: Cr=10.75%, Ni=8.09%, Co=6.64%, Mo=2.99%, Si=0.26%, Mn=0.21%, and the balance is Fe and inevitable impurities.

4. A method for preparing the solid solution strengthened maraging stainless steel for low temperature environment according to any one of claims 1 to 3, characterized in that: The steps include: Step 1: Select metals Cr, Co, Mo, Ni, Mn, Si according to the weight percentage of each element in any one of claims 1 to 3, and the rest is pure iron and inevitable impurities; Step 2: performing vacuum induction melting on the metal elements obtained in step 1, and then performing vacuum consumable remelting to obtain a casting; Step 3: subjecting the ingot obtained in step 2 to high temperature homogenization treatment to obtain a homogenized ingot; Step 4: rolling the homogenized ingot obtained in step 3 to obtain a slab; Step 5: The slab obtained in step 4 is subjected to solution treatment and aging treatment to obtain martensitic aging stainless steel.

5. The method for preparing the solid solution strengthened maraging stainless steel for low temperature environment according to claim 3, characterized in that: In step 2, the smelting is carried out in a vacuum induction melting furnace, the vacuum degree during the whole process is ≤0.1Pa, the refining temperature is 1660-1700MPa, the refining time is ≥1h, and the stirring time is ≥20min.

6. The method for preparing the solid solution strengthened maraging stainless steel for low temperature environment according to claim 3, characterized in that: During the vacuum consumable remelting process in step 2, the vacuum in the furnace is ≤0.01Pa throughout the entire process, and the remelting rate is maintained at 150~300kg / h.

7. The method for preparing solid solution strengthened maraging stainless steel for low temperature environment according to claim 3, characterized in that: The high temperature homogenization process is specifically as follows: Heat in air, the heating method is furnace heating, the heating rate is 100~150℃ / h, keep warm at 1200~1300℃ for 2~4h, then cool to room temperature with water.

8. The method for preparing solid solution strengthened maraging stainless steel for low temperature environment according to claim 3, characterized in that: The rolling process is specifically as follows: The homogenized ingot is heated to 1200° C., the initial rolling temperature T=1100-1150° C., the final rolling temperature T≥1050° C., and the rolling reduction is ≥80%.

9. The method for preparing solid solution strengthened maraging stainless steel for low temperature environment according to claim 3, characterized in that: The solution treatment adopts cyclic solution treatment, specifically: The slab is heated to 750-800°C at a heating rate of 5-10°C / min, kept at this temperature for 0.5h, then cooled to room temperature, and the above solution treatment process is repeated 4 times.

10. The method for preparing the solid solution strengthened maraging stainless steel for low temperature environment according to claim 3, characterized in that: The aging treatment adopts a two-step process, specifically: The first aging treatment temperature is 540~580℃, the aging time is 20~30min, and it is air-cooled to room temperature. The second aging treatment temperature is 480~520℃, the aging time is 40~50min, and it is air-cooled to room temperature.

Citation Information

Cited By

  • Heat treatment method for improving strength and toughness of ultrahigh-strength martensitic steel

    CN121227984A

  • 1500MPa-grade deep-sea high-pressure abrasion-resistant maraging stainless steel plate and manufacturing method thereof

    CN121826521A